Safety and efficacy of simple training protocol in patients after mild traumatic brain injury - Martinikova, Martina; Ruzinak, Robert; Hnilicova, Petra; Bittsansky, Michal; Grendar, Marian; Babalova, Lucia; Skacik, Pavol; Kantorova, Ema; Nosal, Vladimir; Turcanova Koprusakova, Monika; Sivak, Jozef; Sivakova, Jana; et al. (Biomedical papers, 2024)
Aims. Mild Traumatic Brain Injury (mTBI) is the most common type of craniocerebral injury. Proper management appears to be a key factor in preventing post-concussion syndrome. The aim of this prospective study was to evaluate the effect and safety of selected training protocol in patients after mTBI. Methods. This was a prospective study that included 25 patients with mTBI and 25 matched healthy controls. Assessments were performed in two sessions and included a post-concussion symptoms questionnaire, battery of neurocognitive tests, and magnetic resonance with tractography. Participants were divided into two groups: a passive subgroup with no specific recommendations and an active subgroup with simple physical and cognitive training. Results. The training program with slightly higher initial physical and cognitive loads was well tolerated and was harmless according to the noninferiority test. The tractography showed overall temporal posttraumatic changes in the brain. The predictive model was able to distinguish between patients and controls in the first (AUC=0.807) and second (AUC=0.652) sessions. In general, tractography had an overall predictive dominance of measures. Conclusion. The results from our study objectively point to the safety of our chosen training protocol, simultaneously with the signs of slight benefits in specific cognitive domains. The study also showed the capability of machine learning and predictive models in mTBI patient recognition.
Keywords: mild traumatic brain injury; training; tractography; predictive model; machine learning